Genome-wide association study of corneal biomechanical properties identifies over 200 loci providing insight into the genetic etiology of ocular diseases. (27th July 2020) - Simcoe, Mark J; Khawaja, Anthony P; Hysi, Pirro G; Hammond, Christopher J; ,
Abstract: Corneal hysteresis and corneal resistance factor are parameters that reflect the dynamic biomechanical properties of the cornea and have been shown to be biomarkers of corneal disease. In this genome-wide association study of over 100 000 participants, we identified over 200 genetic loci, all but eight novel, significantly associated with either one or both of these traits. In addition to providing key insights into the genetic architecture underlying normal corneal function, these results identify many candidate loci in the study of corneal diseases that lead to severe visual impairment. Additionally, using Mendelian randomization, we were able to identify causal relationships between corneal biomechanics and intraocular pressure measurements, which help elucidate the relationship between corneal properties and glaucoma.